2000
DOI: 10.1179/030192300677705
|View full text |Cite
|
Sign up to set email alerts
|

Effect of alumina pickup on mould flux viscosity in continuous slab casting

Abstract: In the present work, the amount of alumina pickup in sequence casting was evaluated, and the effect on mould Mould flux samples were taken from a continuous flux viscosity quantified. Changes in crystallisation were slab caster mould at various stages during casting also assessed, and will be presented in a future paper. sequences. These confirmed that the amount of alumina pickup reaches a steady state level within the first 40 min of casting (in agreement with a EXPERIMENTAL PROCEDURE simple model of alumina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…In both cases, steady state compositions are achieved within 20 min of the start of the cast, similar to alumina pickup by carbon steel mould fluxes (it was shown that the time constant of the change in composition is approximately equal to the time required for one exchange of the pool of molten mould flux through flux consumption and replacement by fresh powder). 13 Investigation of polished mould flux samples by SEM showed no sign of titanium nitride (Fig. 3), nor was this phase detected by X-ray diffraction.…”
Section: Resultsmentioning
confidence: 96%
“…In both cases, steady state compositions are achieved within 20 min of the start of the cast, similar to alumina pickup by carbon steel mould fluxes (it was shown that the time constant of the change in composition is approximately equal to the time required for one exchange of the pool of molten mould flux through flux consumption and replacement by fresh powder). 13 Investigation of polished mould flux samples by SEM showed no sign of titanium nitride (Fig. 3), nor was this phase detected by X-ray diffraction.…”
Section: Resultsmentioning
confidence: 96%
“…Considerable efforts and optimization [5][6][7][8][9][10] have been carried out to study and suppress these changes in compositions and properties of mold fluxes for high-Al steel based on conventional CaO-SiO 2 system mold fluxes. However, no effective solutions to these problems are proposed based on the conventional CaO-SiO 2 system.…”
Section: Reactionmentioning
confidence: 99%
“…[10,11] This behavior may be due to the following factors: (i) The consumption of mold powder when casting Incoloy 800 is about 0.9 kg t À1 , which is considerably higher than the consumption of mold flux, about 0.3-0.5 kg t À1 [12,13] when casting traditional grades. Figure 7 shows the changes in melting behavior and viscosity of mold flux during continuous casting of Incoloy 800.…”
Section: Compositional Changes In the Mold Flux During Castingmentioning
confidence: 99%